Inguinal Hernia Development in Very Low-Birth-Weight Infants: A Case–Control Study - Unal, Sezin; Isik, Dilek Ulubas; Bas, Ahmet Yagmur; Arslan, Zehra; Demirel, Nihal (European Journal of Pediatric Surgery, 2017)
Introduction The incidence and risk factors for inguinal hernia (IH) is not a thoroughly evaluated issue of preterms. Prematurity is the single most important risk factor. There exists no study in our country which reported the incidence of IH in preterms. The purpose of this study is to investigate the incidence and time of diagnosis of IH in very low-birth-weight (VLBW) infants.Patients and Methods This retrospective case–control study was conducted in Etlik Zubeyde Hanim Women's Health Training and Research Hospital and included discharged VLBW infants with gestational age less than 32 weeks. Control group included gender, birth weight, and gestational age matched VLBW infants without IH.Results The incidence of IH was 10.1% in VLBW infants (70/693) and 16.1% in extremely low-birth-weight infants (19/174). Male/female ratio was found as 3.4:1. Most IH appeared as bilateral (40.0%). Time of diagnosis was 39 (37–42) weeks of postmenstrual age while 68.6% of infants were diagnosed after discharge. IH development increased by 2.3-folds by having respiratory distress syndrome and by 4.5 folds by achieving full enteral feeds on or after the 10th day.Conclusion Preterms with respiratory distress syndrome and those reach full enteral feeding on or after the 10th day should be monitored carefully for IH development. Bearing in mind that a significant amount of IH cases exhibit symptoms after discharge, neonatologists should inform the parents of premature infants of the issue and close attention should be paid in postdischarge follow-up examinations.
Keywords: very low-birth-weight infants; inguinal hernia; neonate; respiratory distress syndrome